Effect of Performance Assessment and Compensation on Lecturer and Employee Productivity in The Faculty of Education and Science North Sumatera Islamic University - Siregar, Melinda (International Journal for Educational and Vocational Studies, 2019)
Performance Appraisal is an effort to identify, measure (assess) and manage (management) to determine decisions about success or failure in carrying out work carried out by workers with work standards set by the company. Compensation for organizations / companies means rewards / rewards to workers who have contributed in realizing their goals, through activities called work. Total productivity is nothing but the ratio of what is produced (out put) to all what is used (in put) to obtain these results. FKIP-UISU Medan is part of one of the faculties at the Islamic University of North Sumatra Medan and its address at Jalan Puri Number 18 Simpang Jalan Alloy Tenaga Medan. The problem formulation is "How big is the effect of performance appraisal and compensation on the productivity of lecturers and staff at the Teaching and Education Faculty of the Islamic University of North Sumatra".The purpose of this study was to determine the FKIP-UISU lecturer and staff assessment of performance appraisals, compensation provided, level of productivity. The results of the study using the formula of multiple correlation between variables x1 (performance appraisal) and x 2 (compensation) together with variable y (productivity of lecturers and staff) that is 0.826 which means it has a positive relationship because r count is greater than rtable (0.826> 0.361 ).  Based on the table, it is known that = 0.826 is at the coefficient interval 0.80 - 1,000, then the relationship of variable x1 (performance appraisal) with variable x2 (compensation) which is jointly correlated with variable y (lecturer and employee productivity) is included in the category very strong relationship. Based on the calculation of the value of Fcount = 28.890 this value is then consulted with Ftable with an error rate of 5% based on the numerator dk = k (2) and the denominator dk = n-k-1 (27), then Ftable = 3.35 is obtained. These results indicate that Fcount is greater than Ftable, 28.890> 3.35. Because the price of Fcount is far greater than the price of Fable, the proposed Zero Hypothesis (H0) is rejected and the Alternative Hypothesis (Ha) is accepted. According to the results of these calculations it can be concluded that the productivity of lecturers and staff at the Teaching and Education Faculty of the Islamic University of North Sumatra, Medan is influenced by performance evaluation and compensation variables of 68.15%, while 31.85% is influenced by other variables.